Modeling of Cooling Curves in Zn-Al Diluted Alloys - Gueijman, Sergio F. (2013)
In this paper we analyze the effect of size and the movement of a zone of coexistence of two phases which release latent heat during solidification on the cooling curves of pure Zn and Zn-1wt.%Al; Zn-2wt.%Al; Zn-3.wt%Al; Zn-4wt.%Al and Zn-5.wt%Al alloys. In samples solidified predominantly unidirectionally it was determined that by the effect of solidification of any portion of the metallic material, either the cooling curves of the alloy in the liquid state or the cooling curves of the solid formed after solidification, a deformation due to thermal effects from mobile sources that release energy occurs. This significantly affects the temperature versus time curves and the form of growth of solids formed during the phase change; hindering the modeling of cooling curves to make them dependent, in addition to time, the properties of the alloy, the particular position in the cylindrical sample, the positions of [(Liquid) / (Solid + Liquid)] and [(Solid + Liquid) / (Solid)] interphases; also, the size of the zone of solid-liquid coexistence, as well as the amount of latent energy released by that zone and segregation of alloying elements, among other factors. F or the samples of specified concentrations, the increases in the temperature of cooling liquid due to overheating thereof, ahead of the [(Liquid) / (Solid + Liquid)] interphase were determined. Also, the increases in the solid temperature due to heat buildup behind the [(Solid + Liquid) / (Solid)] interphase as a function of time and position were determined.